Chapter «Al privato onesto un'arma legittima». Per una genealogia della legittima difesa tra il moderamen inculpatae tutelae e la difesa legittima del diritto penale fascista - Siciliano, Domenico (Studi e saggi, 2020)
The contribution is meant to reconstruct the crucial passage from the 'liberal' conception of self defence (e.g.: Carrara) to that of the Positive School (for all: Fioretti), which was further articulated by Fascist criminal legal doctrine (Manzini, the Rocco brothers) and imposed with the Italian penal code of 1930. The former conception, in the wake of Beccaria and his thematisation of crime as a political and social problem, does not fundamentally allow the deadly self-defence in the protection of property. For the latter, the 'subjects' have a 'right' to defend their property, and with it society, even by deadly force. The contribution highlights the partially dissonant voice of the Court of Cassation, which in one opinion reminded the Fascist state the intrinsic weakness of such a conception